Mutations in ribosomal proteins, RPL4 and RACK1, suppress the phenotype of a thermospermine-deficient mutant of Arabidopsis thaliana. - Jun-ichi Kakehi; Eri Kawano; Kaori Yoshimoto; Qingqing Cai; Akihiro Imai; Taku Takahashi (PLoS ONE, 2015)
Thermospermine acts in negative regulation of xylem differentiation and its deficient mutant of Arabidopsis thaliana, acaulis5 (acl5), shows excessive xylem formation and severe dwarfism. Studies of two dominant suppressors of acl5, sac51-d and sac52-d, have revealed that SAC51 and SAC52 encode a transcription factor and a ribosomal protein L10 (RPL10), respectively, and these mutations enhance translation of the SAC51 mRNA, which contains conserved upstream open reading frames in the 5' leader. Here we report identification of SAC53 and SAC56 responsible for additional suppressors of acl5. sac53-d is a semi-dominant allele of the gene encoding a receptor for activated C kinase 1 (RACK1) homolog, a component of the 40S ribosomal subunit. sac56-d represents a semi-dominant allele of the gene for RPL4. We show that the GUS reporter activity driven by the CaMV 35S promoter plus the SAC51 5' leader is reduced in acl5 and restored by sac52-d, sac53-d, and sac56-d as well as thermospermine. Furthermore, the SAC51 mRNA, which may be a target of nonsense-mediated mRNA decay, was found to be stabilized in these ribosomal mutants and by thermospermine. These ribosomal proteins are suggested to act in the control of uORF-mediated translation repression of SAC51, which is derepressed by thermospermine.